Pengaruh Biaya Produksi dan Harga Jual Terhadap Pendapatan Petani Sayur di Kecamatan Kontukowuna Kabupaten Muna - Wa Ode Titin Hartini; Hapsawati Taan; Djoko Lesmana Radji (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This research aims to find out how much influence distribution channels and selling prices have on the income of vegetable farmers in Kontukowuna District, Muna Regency.The population of this research is vegetable farmers in Kontukowuna District, Muna Regency. The sampling technique used was stratified random sampling. The number of samples in this study using the Slovin formula was 90 respondents. Data collection uses questionnaires and interviews. Data analysis using multiple linear regression analysis.The research results show that, (1) Production Cost have a positive and significant effect on the income of vegetable farmers; (2) Selling prices have a positive and significant effect on vegetable farmers' income, (3) Distribution channels and selling prices both have a significant effect on vegetable farmers' income. This shows that distribution channels and selling prices will influence Production Cost. Production Cost and good selling prices are important in efforts to increase the income of vegetable farmers.